Assembling the Career Firefighter Health Study cohort: A methods overview. Issue 8 (10th June 2021) - Zeig‐Owens, Rachel; Singh, Ankura; Triplett, Suzanne; Salako, Joke; Skerker, Molly; Napier, Ariana; Peele, Eric; Stanley, Marshica; Sattaluri, Sridevi; Prezant, David; Webber, Mayris P.
Abstract: Background: Studies of World Trade Center (WTC)‐exposed rescue/recovery workers report the increased occurrence of health conditions after work at the WTC disaster site. However, the extent to which these associations are due to WTC exposure is unclear, in part due to the lack of suitable comparison groups. Accordingly, we identified a previously assembled National Institute for Occupational Safety and Health (NIOSH) cohort of career firefighters from three US cities ( n = 29, 992). Here, we document the challenges in establishing this non‐WTC‐exposed firefighter cohort for the goal of tracking and comparing cancer and chronic health conditions in WTC‐exposed and non‐WTC‐exposed firefighters. Methods: Follow‐up process included institutional review board applications, data use agreements, state cancer registry linkages and vital status determination for the NIOSH firefighter cohort. After completion of these steps, we undertook outreach to the three original city fire departments and union officials, before contact tracing and direct recruitment of 14, 566 living firefighters to complete a confidential health survey. We staggered recruitment efforts by the city, using letters, postcards, emails, videos, and telephone outreach. Participants who completed the survey received 10. Results: A total of 4962 of 14, 566 alive firefighters responded to the baseline survey (34.1% response rate). Respondents were older and more likely to be non‐Hispanic white than nonrespondents. Conclusions: We provide an overview of the process for the first survey to collect information on physical and mental health conditions among US firefighters. The data collected will have an important impact on studies of WTC rescue/recovery work, firefighting, and related health conditions.